Toward user awareness and acceptance of Sudan E-government: adoption and security perspective - Khalifa, Othman Omran; Hassan, Rasha (2016)
E-government provides delivery of public services in a much more convenient and costeffective way, offering huge opportunities to improve public sector efficiency. The aim of this paper is to examine the citizens’ awareness and acceptance of Sudan e-government adoption and security perspective in Sudan. The study followed empirical research that utilized quantitative method conducting a case study in Sudan e-government, a questionnaire designed to meet the study objectives, data are collected from freshman students as a citizen’s sample who are use online admission to universities as an e-government services, questions were asked to provide insights of accepting adopter of e-government initiatives. The findings revealed that Sudan citizens accept the use of e-government and they are fairly familiar with e-government services, however they are not aware of security aspects and afraid to use the online services. The study recommend to use a biometric fingerprint instead of traditional passwords to increase secure access and authentication.